Flame retardancy and combustion performance of polysaccharide fabrics: A comparison on cotton and calcium alginate fabrics - Ying-Jun Gao; Wen-Jie Jin; Shan-Fei Liu; Xian-Wei Cheng; Jin-Ping Guan; Xu-Hong Yang (Polymer Testing, 2023)
Cotton and calcium alginate (CA) fibers are both polysaccharide-based fibers, but they possess different flame retardancy. The detailed comparisons on flame retardancy and combustion behavior of polysaccharide fabrics are of interest. In this study, the difference between the fabrics made of these two fibers in the combustion process, pyrolysis products and the morphology and chemical structures of char residues were performed by vertical burning, thermal gravimetric analysis, Fourier Transform Infrared Spectrometer (FTIR) and scanning electron microscopy. Compared with cotton fabric, CA fabric had no after-flame when it was burned vertically, and the smoldering time was longer. Especially, the smoke release rate, peak heat release rate and total heat release were much lower versus cotton fabric, indicating that CA fabric had much lower fire hazards than cotton fabric. The results of thermogravimetric analysis coupled with FTIR (TG-FTIR) suggested that CA fabric exhibited a different thermal degradation pathway versus cotton fabric. Under the same quality, CA fabric produced more char residues after combustion, and chrysanthemum-like calcium oxide were generated on the surface of char residues as protective barrier, leading to the enhanced flame retardancy of CA fabric.